Power Relations in the Design and Development of Karangwaru Riverside Yogyakarta-Indonesia – Women's Perspective - Artbanu Wishnu Aji; Suastiwi Triatmodjo; Agus Burhan (Institut Seni Indonesia Yogyakarta, 2022)
The design and construction of riverbanks in Karangwaru is a community participation-based development program where stakeholders play a role in the preparation of development and its implementation. The involvement of women as one of the stakeholders is one of the positive efforts for gender equality programs. However, women's voices in percieving the results of such development have never been clearly explored. How women respond to the development process and how power relations are created in a built environment are yet to be revealed. This study aims to see how power relations are formed in the design and development of Karangwaru Riverside. Using the Foucauldian discourse analysis method, this study managed to find 7 (seven) constructs and discourses that surround them. The results show that women have only control over two discourses, namely ethical and social discourse. Desain dan pembangunan bantaran sungai di Karangwaru merupakan program pembangunan berbasis partisipasi masyarakat di mana pemangku kepentingan berperan dalam persiapan pembangunan dan pelaksanaannya. Keterlibatan perempuan sebagai salah satu pemangku kepentingan merupkan salah satu upaya positif bagi program penyetaraan gender dalam pembangunan. Meskipun demikian suara perempuan dalam melihat hasil pembangunan tersebut belum pernah dieksplorasi dengan jelas. Bagaimana perempuan menyikapi proses pembangunan dan bagaimana relasi kuasa yang tercipta dalam lingkungan terbangun masih belum terungkap. Penelitian ini bertujuan untuk melihat bagaimana relasi kuasa yang terbentuk dalam desain dan pembangunan Karangwaru Riverside. Dengan menggunakan metode analisis diskursus Foucauldian, penelitian ini berhasil menemukan 7 (tujuh) konstruk dan diskursus yang melingkupinya. Hasilnya menunjukkan bahwa perempuan hanya memiliki kontrol pada dua diskurus yaitu diskursus etika dan sosial.